EXTRACTIVE SPECTROPHOTOMETRIC DETERMINATION OF IRON (III) WITH 5-(P-HYDROXYBENZYLIDENE)-THIAZOLIDINEDIONE-2,4 - N. A, Verdizade; K. A, Kuliev; K. R., Alieva (IJRDO-Journal of Applied Science, 2016)
5-(p-hydroxybenzylidene)-Thiazolidinedione-2,4 (L) as a photometric reagent for the extractive spectrophotometricdetermination of iron(III) is presented in this paper. The reagent L gave instantaneous andstable red colour with iron (III) in the pH range 3.8 to 5.2. The Beer’s law was applicable in the range of0.05 - 3.2μg/ml at 535 nm. The Limit of Detection (LOD) is found to be 12 ng/mL. The stoichiometry ofthe complex is established as 1:2 (Fe: L) by equilibrium shift method. The standard deviation and thecoefficient of variance are presented. The results of the prescribed procedure applied for the determination ofthe micro amounts of Fe (III) in pharmaceutical, food and in plant samples are presented.